Respuesta :
Answer:
[tex]f(n) = 3 * 2^{n-1}[/tex] for [tex]n \geq 1[/tex]
Step-by-step explanation:
Given
[tex]f(1) = 3[/tex]
[tex]f(n) =2f(n-1)[/tex]
Required
Determine f(n)
When n = 2
[tex]f(2) = 2 * f(2 -1)[/tex]
[tex]f(2) = 2 * f(1)[/tex]
[tex]f(2) = 2 * 3[/tex]
[tex]f(2) = 6[/tex]
When n = 3
[tex]f(3) = 2 * f(2)[/tex]
[tex]f(3) = 2 * 6[/tex]
[tex]f(3) = 12[/tex]
When n = 4
[tex]f(4) = 2 * f(3)[/tex]
[tex]f(4) = 2 * 12[/tex]
[tex]f(4) = 24[/tex]
List out f1 to f4
[tex]f(1) = 3 * 2^{1-1}[/tex] = 3
[tex]f(2) = 3 * 2^{2-1}[/tex] = 6
[tex]f(3) = 3 * 2^{3-1}[/tex] = 12
[tex]f(4) = 3 * 2^{4-1}[/tex] = 24
[tex]f(n) = 3 * 2^{n-1}[/tex] for [tex]n \geq 1[/tex]
The nth term of the sequence is 3n
Given the recursive function expressed as:
f(n)=2f(n−1)
f(1) = 3
Get the second term:
f(2) = 2f(1)
f(2) = 2(3)
f(2) = 6
Get the third term;
f(3) = 2f(2)
f(3) = 2(6)
f(3) = 12
This form a sequence 3, 6 , 12...
The nth term of the sequence is an = a + (n-1)d
an = 3 + (n - 1)*3
an = 3+(3n-3)
an = 3 + 3n - 3
an = 3n
Hence the nth term of the sequence is 3n
Learn more on sequence here;https://brainly.com/question/18600443